Descriptive Strength and Range of Motion in Youth Baseball Players - Ross M Nakaji; Todd S Ellenbecker; Kevin M McClenahan; Lianna M Roberts; Chase Perez; Scott B Dickenson (North American Sports Medicine Institute, 2021)
# Background There are limited studies reporting descriptive strength and range of motion in youth baseball players 12 years of age or younger. # Purpose To establish normative data for external (ER) and internal (IR) rotation range of motion (ROM), total arc range of motion (TROM), and isometric rotator cuff strength in youth baseball players, and to compare between the dominant throwing arm (D) to the non-dominant arm (ND). # Study Design Cross-sectional # Methods Patient population included 50 (5 to 12-year-old) uninjured, healthy athletes. ROM measurements were performed preseason using a goniometer for IR and ER in the supine position with the shoulder in 90 degrees of abduction (abd) with scapular stabilization. Isometric strength measurements for IR and ER were collected in both neutral and 90 degrees (deg) of abduction with the use of a hand-held dynamometer and recorded in pounds (lbs) utilizing a "make" test. Descriptive statistics were obtained for all measures. # Results All data were analyzed as a single group (average age: 9.02). No significant difference in average total arc of PROM (ER+IR=Total Arc) on the D side compared to the ND side (136.7 ± 12.7 deg vs. 134.3 ± 12.3 deg). There were statistically significant differences between ER ROM (102.2 ± 7.7 deg vs. 96.8 ± 7.4 deg) and IR ROM (34.4 ± 9.0 deg vs. 37.5 ± 9.5 deg) between D versus ND arms (p= .000, .006 respectively). Mean ER strength in neutral (13.6 ± 3.4 and 12.8 ± 3.6 lbs) and 90 deg abduction (12.3 ± 3.4 and 12.5 ± 4.3 lbs) did were not significantly different between D and ND arms, respectively. Mean IR strength in neutral (18.0 ± 6.0 and 15.7 ± 4.7 lbs) and 90 deg abd (16.4 ± 5.6 and 15.0 ± 5.7 lbs) was significantly greater in the D arm vs ND arm, respectively (p=.000, .001). # Conclusion These data can provide descriptive information for clinicians who treat very young baseball players. These data show sport specific adaptations occur at very young ages (5-12) and are similar to prior reports on adolescent, high school and professional baseball players regarding upper extremity ROM and rotator cuff strength. # Level of Evidence 3